ROTI KETAWA: SIMBOL BUDAYA DAN KEUNIKAN KULINER KOTA PEMATANGSIANTAR - Fahmi Ramadhan; Ria Pinola Sari; Lestari Dara Cinta Utami Ginting; Lila Pelita Hati (JISOS: JURNAL ILMU SOSIAL, 2024)
This research aims to investigate the history, cultural influence, and economic role of Roti Ketawa as a typical souvenir of Pematangsiantar City. This research method uses a historical approach by collecting sources from the internet, journals, and through interviews with business owners and consumers of Roti Ketawa. In addition, interview techniques were also carried out with a number of respondents who were experienced in the production and consumption of Roti Ketawa. Qualitative data analysis is used to summarize information from interviews and sources collected. From the results of this study, it is concluded that Roti Ketawa is not only an ordinary culinary product, but also a symbol of joy and optimism that plays an important role in shaping the city's identity. Roti Ketawa also makes a significant contribution to the local economy and tourism, making it an attraction for tourists. However, sales of Roti Ketawa face challenges in attracting the younger generation as consumers. The implications of these findings can help Roti Ketawa business owners in designing marketing strategies that are more appealing to the younger generation. In addition, local governments can also utilize this information to support tourism promotion and local economic development in Pematangsiantar City